If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7 + 9g + -8 + 2g = 0 Reorder the terms: 7 + -8 + 9g + 2g = 0 Combine like terms: 7 + -8 = -1 -1 + 9g + 2g = 0 Combine like terms: 9g + 2g = 11g -1 + 11g = 0 Solving -1 + 11g = 0 Solving for variable 'g'. Move all terms containing g to the left, all other terms to the right. Add '1' to each side of the equation. -1 + 1 + 11g = 0 + 1 Combine like terms: -1 + 1 = 0 0 + 11g = 0 + 1 11g = 0 + 1 Combine like terms: 0 + 1 = 1 11g = 1 Divide each side by '11'. g = 0.09090909091 Simplifying g = 0.09090909091
| 3x-(9)=75+x | | 3x-2+2x+4+x+10=o | | -61=12a-1 | | 3x^2+3y^2=6 | | 53=5-2u | | 1-8k-9k-4= | | 29-4x=4 | | 2y+9fory=-6 | | 6f-7f-1=-5-5f | | 3a+a+25=225 | | 2+2x-5=5x+3 | | x+7+3x-1+2x+5=0 | | 5-y=-2x-5 | | X=32+2x | | 4x*1=0 | | -q=8+q | | 23x^2+50x+25=0 | | 2x+(x+1)=4 | | m^3+4=1 | | 2x+x+1=4 | | 0.2f=-8.4 | | -12(2-t)=14t | | 4v+10+v-9= | | x+6(4)=29 | | (2d-7)=(2+4d)2 | | a+.75a=21 | | 0=2x^2+1x-6 | | 3x+17+3+7x=x | | 2(-6y+29)-4y=-6 | | (2(23)+21)= | | y,5-6=8 | | 3+n^3=6 |